INNOVATIVE RESEARCH ABOUT SCHOOL TEACHERS STRESS AND SUSTAINABLE STRATEGIES TO ELIMINATE SCHOOL TEACHERS STRESS - SUMATHY, Dr.V. (International Journal of Psychosocial Rehabilitation, 2020)
The worker’s response to work stress can be either psychological, physical or both and is usually categorized as being acute, post traumatic, or chronic. National surveys in the United Kingdom , Australia and India have reported a serious and growing problem of academic work stress with several deleterious consequences including decreased job satisfaction, reduced morale and ill health for academic staff. The outcome of stress may be of: emotional manifestations, dissatisfaction, depression, feelings of undefined anxiety, fear and low self-esteem with a possible extreme result being burnout; behavioral manifestations - behavioral issues such as hungry disorders, excessive smoking and alcohol or drug abuse, violence , sleep disorders , possible displays of withdrawal symptoms that is absence and resignations from the profession.